Clip-assisted endoscopic cyanoacrylate injection for gastric varices with a gastrorenal shunt: a multicenter study - Zhang, Mingyan; Li, Ping; Mou, Haijun; Shi, Yongjun; Tuo, Biguang; Jin, Suyun; Sun, Ruonan; Wang, Guangchuan; Ma, Jiali; Zhang, Chunqing (Endoscopy, 2019)
Background The aim of this study was to evaluate the safety and efficacy of clip-assisted endoscopic cyanoacrylate injection for gastric varices with a gastrorenal shunt. Methods Records were reviewed of patients with gastric varices and concomitant gastrorenal shunts who underwent clip-assisted endoscopic cyanoacrylate injection at three tertiary centers between April 2016 and October 2018. The assessed outcomes were technical success rate, eradication of gastric varices, cyanoacrylate embolization, and all-cause rebleeding.Results A total of 61 patients were analyzed. The procedure was successful in all patients (100 %). Gastric varices were eradicated in 30 of 33 patients (90.9 %) according to contrast-enhanced computed tomography re-examination within 1 month after the procedure. No symptoms or signs of cyanoacrylate embolization related to the procedure were observed. Four patients (6.6 %) were lost to follow-up. All-cause rebleeding occurred in 13/57 patients (22.8 %) during a median follow-up period of 225 days (interquartile range 114 – 507 days). Conclusions Clip-assisted endoscopic cyanoacrylate injection appeared to be a safe procedure that was convenient and efficacious in the treatment of gastric varices with concomitant gastrorenal shunt.